1998
DOI: 10.1111/j.1540-6288.1998.tb01367.x
|View full text |Cite
|
Sign up to set email alerts
|

An empirical comparison of bankruptcy models

Abstract: Four types of bankruptcy prediction models based on financial statement ratios, cash flows, stock returns, and return standard deviations are compared. Based on a sample of bankruptcies from 1980 to 1991, results indicate that no existing model of bankruptcy adequately captures the data. During the last fiscal year preceding bankruptcy, none of the individual models may be excluded without a loss in explanatory power. If considered in isolation, the cash flow model discriminates most consistently two to three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(75 citation statements)
references
References 21 publications
1
68
0
3
Order By: Relevance
“…Lastly, the estimated coefficients can be interpreted separately as the importance or significance of each of the independent variables in the explanation of the estimated PD. After the work of Ohlson (1980), most of the academic literature (Zavgren (1983), Gentry et al (1985), Keasey and Watson (1987), Aziz et al (1988), Platt and Platt (1990), Ooghe et al (1995), Mossman et al (1998), Charitou andTrigeorgis (2002), Lizal (2002), Becchetti and Sierra (2002)) used logit models to predict default. Despite the theoretic differences between MDA and logit analysis, studies (see for example Lo (1985)) show that empirical results are quite similar in terms of classification accuracy.…”
Section: Default Prediction Studiesmentioning
confidence: 99%
“…Lastly, the estimated coefficients can be interpreted separately as the importance or significance of each of the independent variables in the explanation of the estimated PD. After the work of Ohlson (1980), most of the academic literature (Zavgren (1983), Gentry et al (1985), Keasey and Watson (1987), Aziz et al (1988), Platt and Platt (1990), Ooghe et al (1995), Mossman et al (1998), Charitou andTrigeorgis (2002), Lizal (2002), Becchetti and Sierra (2002)) used logit models to predict default. Despite the theoretic differences between MDA and logit analysis, studies (see for example Lo (1985)) show that empirical results are quite similar in terms of classification accuracy.…”
Section: Default Prediction Studiesmentioning
confidence: 99%
“…Investigation on cash flows revealed that many authors (Carslaw & Mills 1991) (Mills & Yamamura 1998) (Mossman & Bell 1998) agree on the importance of cash flow information. Cash flow may be viewed as the lifeblood of a company and the essence of its very existence (Rujoub, Cook & Hay 1995).…”
Section: The Importance Of Cash Flow Informationmentioning
confidence: 99%
“…Further, when evaluating the discriminatory ability of each of the models, the authors found that while the cash-flow model produced consistent results as much as three years prior to bankruptcy, the Z-score model performed better in the final year prior to failure. As such, it would appear that cash-flow characteristics may provide advance warning of potential future problems, while ratio analysis is best at predicting imminent failure (Mossman, Bell, & Swartz, 1998).…”
Section: Implications For Causes Of Failurementioning
confidence: 99%